PENGARUH AUDIT TENURE, PERTUMBUHAN PERUSAHAAN, UKURAN PERUSAHAAN, REPUTASI KAP, DAN OPINION SHOPPING TERHADAP OPINI GOING CONCERN PADA PERUSAHAAN MANUFAKTUR DI BEI - Ahfas , Mahfuz (Accounting Research and Business Journal, 2023)
ABSTRACT Companies that get going concern opinions from auditors are caused by conditions and events that raise doubts about the survival of a company. Going concern audit opinion is an early warning for users of financial statements to avoid making wrong decisions. There are many previous studies on financial and non-financial factors that influence the acceptance of going-concern audit opinions in manufacturing companies, but apart from that there are also different results which say there is no effect on going-concern audit opinions. Therefore, researchers want to further examine the going concern audit opinion. IDX 2019-2022